Finansial Performance Analysis of the Regional Government of Enrekang Regency for Fisical Tears 2018-2020 - Nur, Yustika; Haeril, Haeril; Albar, Albar; Kurnia M, Fakhruddin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research is a quantitative descriptive study conducted at the Enrekang Regency Government with the title Financial Performance Analysis of the Enrekang Regency Government for the 2018–2020 Fiscal Year. The purpose of this study is to determine and analyze the financial performance of the local government of Enrekang Regency over the last three years (2018–2020), using data from the Budget Realization Report of the Enrekang Regency Government for the 2018–2020 Fiscal Year. The analytical tools used in this research include the Regional Financial Independence Ratio, the Effectiveness and Efficiency Ratio of Regional Original Income, the Activity Ratio, the Growth Ratio, the Decentralization Ratio, and the Regional Financial Dependence Ratio. The results show that the financial performance of the Enrekang Regency Government is characterized by: (1) a low Regional Financial Independence Ratio, averaging 30.77%; (2) an ineffective Effectiveness Ratio, averaging 57.33%; (3) a very efficient Efficiency Ratio, averaging 3.4%; (4) poor capital expenditure performance with an average of 20.51% and good operational expenditure performance with an average of 79.17%; (5) low income growth, averaging 17.17%, and low expenditure growth, averaging 3.67%; and (6) a Decentralization Ratio that, in general, indicates that decentralization has not yet been effectively implemented.